Deskripsi Kode Etik Guru Pendidikan Agama Kristen dalam Perspektif Alkitabiah: Sebagai Keteladan Akademik dan Karakter Nara Didik - Desi Ratnasari; Reni Triposa; Yonatan Alex Arifianto (Sekolah Tinggi Teologi Real Batam, 2022)
The code of ethics in the Biblical perspective for teacher’s Christian religious education is an important part of actualizing education. Because the code of ethics brings teachers to be able to understand the students well. Christian education, which is still lacking in the application of ethics for teachers, is a challenge in itself. The purpose of this study is to provide understanding to teachers of Christian religious education so that in the learning process provide a good example for students. This research uses qualitative methods. The result of the research is that teachers before educating must be equipped with truth values that are in accordance with God's word. Being a teacher is not only a teacher but as a guide to the character of students to be a character that is pleasing before the Lord Jesus. Christian teachers before educating must properly learn the teacher's code of ethics in accordance with the biblical perspective. When Christian teachers have understood the correct code of ethics, in every teaching and guidance done to the students can go well in accordance with the truth of God's word.Keywords: biblical; teachers; character; code of ethics; studentsAbstrakKode etik dalam perspektif Alkitab bagi guru Pendidikan agama Kristen menjadi bagian penting dalam mengaktualisasikan pendidikan. Sebab kode etik tersebut membawa guru mampu memahami nara didik dengan baik. Pendidikan Agama Kristen yang masih kurang dalam penerapan etika bagi guru menjadi tantangan tersendiri. Tujuan dari penelitian ini untuk memberikan pemahaman kepada guru Pendidikan agama Kristen agar dalam proses pembelajaran memberikan keteladan yang baik bagi nara didik. Penelitian ini menggunakan metode kualitatif. Hasil dari penelitian adalah guru sebelum mendidik harus dibekali dengan nilai-nilai kebenaran yang sesuai dengan Firman Tuhan. Menjadi guru bukan hanya sebagai pengajar tetapi sebagai pembimbing karakter siswa-siswi menjadi karakter yang berkenan di hadapan Tuhan Yesus. Guru agama Kristen sebelum mendidik harus memperlajari dengan baik kode etik guru sesuai dengan prespektif Alkitabiah. Ketika guru agama Kristen sudah memahami kode etik yang benar maka dalam setiap pengajaran dan pembimbingan yang dilakukan kepada para murid dapat berjalan dengan baik sesuai dengan kebenaran Firman Tuhan.Kata kunci: alkitabiah; guru; karakter; kode etik; murid